COGNITIVE-BEHAVIORAL THERAPY FOR GENERALIZED ANXIETY AND SEPARATION ANXIETY DISORDERS: AN ANALYSIS OF THE EFFECTIVENESS - Orgilés Amorós, Mireia; Méndez Carrillo, Francisco Xavier; Rosa Alcázar, Ana Isabel; Inglés Saura, Cándido José (Anales de Psicología / Annals of Psychology, 2003)
The purpose of this article is to review the effectiveness of the treatment of generalized anxiety and separation anxiety disorders in children and adolescents. Eight scientific reports from 1980 to 2002 were found and led to 21 independent studies. Six hundred and sixty two subjects, between the ages of 7 and 14, with an average age of 10,5 years, took part. The results revealed that cognitivebehavioral therapy and cognitive behavioral therapy plus family anxiety management are probably efficacious treatments, in base to the criteria of the American Psychological Association´s Division 12, Clinical Psychology (Task Force on Promotion and Dissemination of Psychological Procedures, 1995). One of the most effective programs for the treatment of these problems is described. Finally, some variables which could influence in the effectiveness of the treatments, some conclusions and future directions for research in this area are included.